Diseño de un sistema de costos por procesos para la empresa embotelladora de agua de manantial purificada H-VIDA. - Navia Pisco, Anyela Marianela (2019)
Actually, a frequent problem of small and medium enterprises is the lack of real and timely financial information. This information can propitiate an efficient instrument for right decision making. The overall objective of the project is the Design of a Process Cost System for the H-VIDA purified spring water bottling company. The study contains an applied research of a descriptive nature, with a non-experimental field design. For effect, data collection techniques were used, such as direct observation, structured interview and review of bibliographic sources. This techniques and instruments allowed to identify the cost elements and times incurred in each stage of the productive process. The obtained information in the research, led to design the cost system such as a key tool for management in making economic and strategic decisions focused on achieving administrative efficiency. It is recommended to apply this process cost system to cover the requirements and reflect the business reality of H-VIDA in order to grow it.